Correlation between visual scores and parathyroid function - Lorente-Poch, Leyre; de Miguel-Palacio, Maite; Sancho-Insenser, Joan (Frontiers in Endocrinology, 2023)
This mini-review summarizes the controversies around routine parathyroid identification and publications assessing visual scores in an attempt to predict parathyroid function after thyroidectomy during the pre-ICG era